2012
DOI: 10.1017/s1743921313002263
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle and quasi-biennial variations in helioseismic frequencies

Abstract: The prolonged period of solar minimum between cycles 23 and 24 has invoked a great deal of interest to understand the origin of the unusually low solar activity. Even though the origin of solar activity is believed to lie in the shear layer at the base of the convection zone, the analysis of helioseismic data seem to orientate us toward the near surface. In this context, we analyze the signature of the quasi-biennial periodicity seen in the oscillation frequencies which may provide additional constraints on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…These periods are consistent with those obtained from the analysis of the entire data, suggesting that both cycles have different dominant QBO periods. The QBO period obtained in cycle 23 confirms the single peak in the power spectrum as reported by Tripathy et al (2013b), with a period of about 2 yr (∼700 days). We also obtain an insignificant hump around a period of 1010 days in cycle 23.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These periods are consistent with those obtained from the analysis of the entire data, suggesting that both cycles have different dominant QBO periods. The QBO period obtained in cycle 23 confirms the single peak in the power spectrum as reported by Tripathy et al (2013b), with a period of about 2 yr (∼700 days). We also obtain an insignificant hump around a period of 1010 days in cycle 23.…”
Section: Resultssupporting
confidence: 84%
“…It is important to mention that the double-peak structure was not identified in earlier studies. For example, Tripathy et al (2013b) reported only a single peak in the global power spectrum by using the oscillation frequencies for cycle 23 and To explore the origin of the two peaks in GWPS, shown in Figure 3, we separated out the frequency shifts for cycles 23 and 24 and calculated the wavelet spectrum and GWPS for both cycles independently. As is evident in Figure 4, the double-peak structure no longer appears in the GWPS; only one peak is obtained in each cycle, but with different QBO period and power; for cycles 23 and 24, the periods are 206 days, respectively.…”
Section: Resultsmentioning
confidence: 99%